Optic neuropathy and congenital glaucoma associated with probable Zika virus infection in Venezuelan patients. (14th March 2018) - De Moraes, C. Gustavo; Pettito, Michele; Yepez, Juan B.; Sakuntabhai, Anavaj; Simon-Loriere, Etienne; Zaidi, Mussaret B.; Prot, Matthieu; Ruffie, Claude; Kim, Susan S.; Allikmets, Rando; Terwilliger, Joseph D.; Lee, Joseph H.; et al.
Abstract : Introduction. Although the current Zika virus (ZIKV) epidemic is a major public health concern, most reports have focused on congenital ZIKV syndrome, its most devastating manifestation. Severe ocular complications associated with ZIKV infections and possible pathogenetic factors are rarely described. Here, we describe three Venezuelan patients who developed severe ocular manifestations following ZIKV infections. We also analyse their serological response to ZIKV and dengue virus (DENV). Case presentation. One adult with bilateral optic neuritis, a child of 4 years of age with retrobulbar uveitis and a newborn with bilateral congenital glaucoma had a recent history of an acute exanthematous infection consistent with ZIKV infection. The results of ELISA tests indicated that all patients were seropositive for ZIKV and four DENV serotypes. Conclusion. Patients with ZIKV infection can develop severe ocular complications. Anti-DENV antibodies from previous infections could play a role in the pathogenesis of these complications. Well-designed epidemiological studies are urgently needed to measure the risk of ZIKV ocular complications and confirm whether they are associated with the presence of anti-flaviviral antibodies.